Nanocarbon or indocyanine green: Which is superior for gasless transaxillary endoscopic thyroidectomy to protect the parathyroid gland? - Zhipeng, Ye; Keren, Wu; zhao, Hu; Fa, Jin (Frontiers in Surgery, 2022)
Background：The damage of parathyroid glands after thyroidectomy still appears commonly, which often result in hypoparathyroidism. It is indispensable to identify the parathyroid glands in thyroid surgical procedures to prevent accidental surgical removal. Methods：All selected participants were randomly divided into three groups. ICG angiography was performed intraoperatively in ICG group and Nano-carbon suspension in Nano-carbon (NC) group to identify and protect parathyroid glands in neck lymph node dissection for patients with thyroid cancer. Surgical outcomes, including operation time, number of lymph nodes, serum calcium and number of Parathyroid Glands were analyzed. Results：In the NC and ICG groups a higher number of parathyroid are revealed and lower incidence of temporary hypoparathyroidism appear than control group. The number of parathyroid in NC group were higher than the ICG group. Conclusions：compared with ICG angiography, gasless insufflation transaxillary endoscopic thyroidectomy with nanocarbon can better enhance the identification of the parathyroid in thyroid cancer surgery, and reduce the risk of mistakenly cutting the parathyroid.